Benefits and barriers of utilizing data in business development - Mäkinen, Lauri (My University, 2025)
The normalization of digitalization and data collection within companies has become more wide spread, but the way companies use data for business development varies significantly between organizations. As a result, companies are increasingly investing in data utilization and digital tools. Simply having a strategy and decisions based on the core business operations are no longer enough to maintain competitive advantage. Companies must also adopt more digital capabilities. Data has become an essential enabler of competitiveness for companies, but the internal processes of the company must be ready for this. This research aims to explore the opportunities and challenges associated with using data for business development and what solutions could be applied to address these issues. The purpose of the research is to identify similarities in these challenges and opportunities through two example companies. The theoretical framework of the study focuses on data strategy, data quality and governance, big data, and how different companies collect data. Previous studies have found that, although companies collect a significant amount of data from both internal and external sources, its use for business development still has room for improvement. Previous research also highlights the role of employees and management as enablers and potential barriers to effective utilization. The research method used was a comparative case study, and data was collected through semi-structured thematic interviews, with a total of six interviews conducted. The interviewees were selected based on their experience in the subject area and their current role in the target company. The research findings indicated that the target companies are increasingly utilizing data, but data fragmentation due to systems and organizational resources limit the potential benefits derived from the data. Despite the fact that the target companies operate in different sectors one being a domestic company and the other a global enterprise the same obstacles were observed in both sets of research materials.
Keywords: data; big data; decision making; business; competitive advantage; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development